Cultivated Mushrooms: A Comparative Study of Antioxidant Activity and Phenolic Content - Mafalda Silva; Manuela Lageiro; Ana Cristina Ramos; Fernando H. Reboredo; Elsa M. Gonçalves (Biology and Life Sciences Forum)
This study compares the total phenolic content (TPC) and antioxidant activity (DPPH, ABTS, and FRAP assays) of methanolic extracts from five cultivated mushroom species: Lentinula edodes (LE), Pleurotus ostreatus (PO), Agaricus bisporus (AgW and AgB), and Hericium erinaceus (HE). Phenolic profiles were analyzed by HPLC. AgW demonstrated the highest TPC (46.2 mg GAE/100 g FW) and superior antioxidant activity in DPPH and FRAP assays, highlighting its phenolic compounds as the primary contributors. Catechin and hydroxybenzoic acid were identified as species-specific phenolics in PO and AgW, respectively, contributing to their antioxidant potential. These findings underscore the diversity of antioxidant mechanisms in mushrooms and their potential as natural sources of bioactive compounds.